Land, soil and water management - Srivastava, K.L.; Astatke, A.; Mamo, T.; Regassa, H.; Kidanu, S. (International Livestock Centre for Africa, 1993)
This chapter reviews relevant Vertisol properties, experimental results and the overall experience of the project on this subject. There are several types of drainage problems in Vertisols whose magnitude may vary from site to site. Drainage improvement is discussed in relation with camber beds, broadbeds and furrows, field depressions, perched watertable, open ditches, height of beds, soil erosion and supplemental irrigation. The need for water shed development projects is also examined.